Quicks - Waltman, Kevin (2016)
"Marion High, an inner-city school in Indianapolis, has never had a state championship. It's D-Bow's Senior Year, his A-Game is ready, big-time colleges are taking notice, and he's dreaming big. What's rattling D-Bow is the cocky white guy, Daryl. He wants D-Bow's job at point. It's time for D-Bow to man up. He needs to be the team leader, and he needs to bring that A-Game"--
Keywords: Basketball stories; High schools -- Juvenile fiction; Schools -- Juvenile fiction; African Americans -- Juvenile fiction; Basketball -- Fiction; High schools -- Fiction; Schools -- Fiction; African Americans -- Fiction; Young adult fiction